Diagnostic performance of food consumption for bacteraemia in patients admitted with suspected infection: a prospective cohort study. Issue 5 (27th May 2021) - Takada, Toshihiko; Fujii, Kotaro; Kudo, Masataka; Sasaki, Sho; Yano, Tetsuhiro; Yagi, Yu; Tsuchido, Yasuhiro; Ito, Hideyuki; Fukuhara, Shunichi
Abstract : Objectives: A previous study reported that food consumption is useful to rule out bacteraemia in hospitalised patients. We aimed to validate the diagnostic performance of (1) food consumption and (2) a previously reported algorithm using food consumption and shaking chills for bacteraemia in patients admitted to hospital with suspected infection. Design: Prospective cohort study. Setting: Department of General Medicine in two acute care hospitals in Japan. Participants: A total of 2009 adult patients who underwent at least two blood cultures on admission. Primary outcome measures: The reference standard for bacteraemia was judgement by two independent specialists of infectious diseases. Food consumption was evaluated by the physician in charge asking the patient or their caregivers the following question on admission: 'What percentage of usual food intake were you able to eat during the past 24 hours?' Results: Among 2009 patients, 326 patients were diagnosed with bacteraemia (16.2%). Diagnostic performance of food consumption was sensitivity of 84.4% (95% CI 80.1 to 88), specificity of 19.8% (95% CI 18 to 21.8), positive predictive value (PPV) of 16.9% (95% CI 15.2 to 18.9) and negative predictive value (NPV) of 86.8% (95% CI 83.1 to 89.8). The discriminative performance was an area under the curve of 0.53 (95% CI 0.50 to 0.56). The performance of the algorithm using food consumption and shaking chills was sensitivity of 89% (95% CI 85.1 to 91.9), specificity of 18.8% (95% CI 17 to 20.7), PPV of 17.5% (95% CI 15.7 to 19.4) and NPV of 89.8% (95% CI 86.2 to 92.5). Conclusion: Our results did not show the usefulness of food consumption and the algorithm using food consumption and shaking chills for the diagnosis of bacteraemia in patients admitted to hospital with suspected infection.